Pengembangan Media Pembelajaran Berbasis Adobe Flash dengan Pendekatan Kontekstual pada Operasi Hitung Bentuk Aljabar - Yoshu Febrian Shandy; Muhammad Win Afgani; Atika Zahra (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2023)
This study aims to look at the validity, practicality and potential effects of computer-based learning media with a contextual approach to algebraic arithmetic operations. The type of research used is Research and Development (R&D). The development research method from Tessmer, which consists of a preliminary stage and a formative evaluation stage (self evaluation, expert review, one to one, small group, and field test). The data collection techniques used were validation sheets, questionnaires, interviews and tests. The subjects in this study were class VII.4 SMPN 9 Palembang students in the one to one and small group stages, while the subjects in the field test stage were class VII.3 students. The results of the study show that computer-based learning media is included in the category of valid, very practical and has potential effects. This is indicated by the average value of the expert validator 4,06 . Based on the practicality questionnaire, the students at the one to one stage were 4.33, the small group was 4.78 and the field test stage was an average of 4.35, which means they are included in the very practical criteria. The potential effect is in the good category based on the students' post test at the field test stage with a percentage of 76%.